Medical Screening and Award Errors in Disability Insurance - Helge Liebert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates the impact of medical screening on individual disability insurance benefit receipt. Using a unique policy change in Switzerland, I assess the size of award errors in disability insurance and show that improvements in medical screening can substantially reduce insurance inflow. In the absence of explicit medical screening, wrongful admissions dominate rejection errors and account for at least 14% of insurance inflow. Misclassification is tied to difficult-to-diagnose conditions, indicating inaccurate assessments by general practitioners. Reductions in full pension benefit awards are potentially substituted in part by increases in partial benefit awards.
Keywords: H53; H55; J14; 330